2022
DOI: 10.1002/mame.202200346
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Recycled Polymers Recovered from Multilayer Plastic Packaging Films by Solvent‐Targeted Recovery and Precipitation (STRAP)

Abstract: Multilayer plastic film use increased in multiple packaging applications due to its versatility and overall increased performance over monolayer structures. However, the performance gains from multiple layers also make recycling difficult because they contain multiple polymers that can be immiscible and burdensome to traditional mechanical recycling operations. A possible solution is the solvent‐targeted recovery and precipitation (STRAP) process, but the effect on the retrieved polymer is still unknown. The S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The upper bound on temperature enables calculations of polymer solubility at elevated temperatures while avoiding temperatures that are too high, which may lead to melting or thermal degradation and thereby influence the properties of the recovered materials. 45,50 Using this approach, we performed large-scale solubility predictions for 8 polymers and 1007 solvents at both temperatures, establishing a solubility database with over 16 000 data points. Table 2 shows some selected results from these solubility predictions for 25 common polymer–solvent systems.…”
Section: Resultsmentioning
confidence: 99%
“…The upper bound on temperature enables calculations of polymer solubility at elevated temperatures while avoiding temperatures that are too high, which may lead to melting or thermal degradation and thereby influence the properties of the recovered materials. 45,50 Using this approach, we performed large-scale solubility predictions for 8 polymers and 1007 solvents at both temperatures, establishing a solubility database with over 16 000 data points. Table 2 shows some selected results from these solubility predictions for 25 common polymer–solvent systems.…”
Section: Resultsmentioning
confidence: 99%
“…Cecon et al characterized polyethylene (PE) and PET resins recovered using the STRAP process and observed that changes in the melting temperature were only noticeable when there was solvent retention in the polymer matrix. 25…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PP and PE are immiscible plastics that are difficult to separate with current recycling practices [ 9 ], which raised the question of how to efficiently recover high-value post-consumer plastics with high purity from single-stream collection. To address this matter and improve the recycling rate and systems, the European Union (EU) has enforced Extended Producer Responsibility (EPR) laws on packaging products since 1994, a recognized efficient waste-management policy that has become more popular in the U.S. Research studies have reported different techniques and processes to recover PP wastes [ 2 ], multilayer packaging films [ 11 ], plastic waste from material recovery facilities [ 12 ], and mixed wastes [ 13 ], aiming to achieve climate change mitigation and a circular economy.…”
Section: Introductionmentioning
confidence: 99%